ANALISIS KUAT TEKAN DAN ULTRASONIC PULSE VELOCITY (UPV TEST) PADA MUTU BETON K 350 MENGGUNAKAN BETON SISA PENGUJIAN SEBAGAI SUBSTITUSI AGREGAT KASAR - Azhar Darujati; Sartika Nisumanti; Ghina Amalia (PADURAKSA: Jurnal Teknik Sipil Universitas Warmadewa, 2023)
One of the efforts to reduce the exploitation of natural rock as a constituent material for concrete is to utilize the concrete left over from the test. The test waste concrete used is leftover concrete or waste from laboratory test results as a substitute for coarse aggregates in the manufacture of new concrete. The purpose of this study is to determine the effect of using the residual concrete of the test as a substitution of coarse aggregates in the concrete mixture against the values of compressive strength and density through the ultrasonic pulse velocity (UPV) test. The research method used in this study is an experimental method by testing the compressive strength of concrete and testing ultrasonic pulse velocity (UPV test). From the test results, the average compressive strength of mixed concrete left over from the test experienced an increase in concrete compressive strength at a variation of 25% by 25.3 MPa, 35% by 26.7 MPa, and 50% by 28.6 MPa, but did not exceed normal concrete by 30.6 MPa. Meanwhile, the results of ultrasonic pulse velocity (UPV) testing experienced an increase in the average rapid propagation of 25% variation waves by 4034.0 m/s, 35% by 4413.7 m/s, 50% by 4589.3 m/s, and normal concrete by 4534.3 m/s. So the higher the compressive strength value of concrete, the higher the UPV test results will be.